The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1516-35982010000300026
|View full text |Cite
|
Sign up to set email alerts
|

Ingestive behavior of Nellore cows and their straightbred or crossbred calves

Abstract: -This trial aimed to investigate the influence of calf genetic group on the ingestive behavior of Nellore dams and their offspring on pasture. Twenty one primiparous and multiparous Nellore cows were assigned to the experiment; 13 cows nursed straightbred Nellore calves; and eight cows nursed halfbred Simmental × Nellore calves. The observations started in the morning, as soon as identification of the animals in daylight was possible, and they lasted until after sunset, when identification became impossible. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In the current study, sex did not affect the duration of rumination in beef calves. This agrees with the findings by Vargas Junior et al [ 58 ] and de Souza Teixeira et al [ 59 ], who reported that sex does not affect rumination activity in Nellore and beef calves.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, sex did not affect the duration of rumination in beef calves. This agrees with the findings by Vargas Junior et al [ 58 ] and de Souza Teixeira et al [ 59 ], who reported that sex does not affect rumination activity in Nellore and beef calves.…”
Section: Discussionsupporting
confidence: 93%
“…When milk production of the dam is not sufficient to meet the demand of the offspring, calves try to compensate for this condition by spending more time grazing [ 54 ]. In this study, milk production and composition did not change between RES and CON cows.…”
Section: Discussionmentioning
confidence: 99%